PENGALAMAN IBU NIFAS YANG MENJALANI PERAWATAN TRADISIONAL BAPASOA DI KELURAHAN MAMBORO BARAT PROVINSI SULAWESI TENGAH - Sinta Gintu; Tigor H. Situmorang; Ni Nyoman Udiani (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2024)
Background: The postpartum is a recovery period after deliver that begins after placenta discharge until the uterus organ recover to pre-pregnancy condition within 6 to 8 weeks. Some of the Kaili tribe people of Mamboro Barat Village still trust to sando mpoana (traditional birth attendants) because they feel save when doing postpartum care at Sando. This study aims to find out in depth about the experiences of postpartum women who undergo Bapasoa traditional care in Mamboro Barat Village, Central Sulawesi Province. Methods: This type of research is qualitative with a phenomenological approach. Data collection by using in-depth interviews aims to obtain data and an overview of the traditions of postpartum women care after giving birth. Research Results: The results of this study obtained 10 themes, such of: 1) Changes in the family environment, 2) Benefits of bapasoa, 3) Side effects, 4) Efforts to prevent the side effects, 5) Efforts to achieve recovery, 6) Types of support, 7) Source of support, 8) Obstacles when going to bapasoa, 9) Efforts to overcome obstacles, 10) Expectations. Conclusion: The experience of postpartum women who undergo bapasoa traditional care is able to adapt to undergoing bapasoa traditional care and requires support from themselves, others and health workers to overcome the obstacles. Suggestion: For local medical personnel, this research can be the basis for conducting health promotion and continuous assistance to postpartum women who undergo bapasoa traditional care.